2008
DOI: 10.1126/science.1159052
|View full text |Cite
|
Sign up to set email alerts
|

Surface Sites for Engineering Allosteric Control in Proteins

Abstract: Statistical analyses of protein families reveal networks of coevolving amino acids that functionally link distantly positioned functional surfaces. Such linkages suggest a concept for engineering allosteric control into proteins: The intramolecular networks of two proteins could be joined across their surface sites such that the activity of one protein might control the activity of the other. We tested this idea by creating PAS-DHFR, a designed chimeric protein that connects a light-sensing signaling domain fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
347
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(363 citation statements)
references
References 36 publications
12
347
0
4
Order By: Relevance
“…The light-regulated affinity was even increased about 64-fold in subsequent rounds of rational mutagenesis (Strickland et al 2010). In a similar way, also a fusion of the LOV domain with the E. coli dihydrofolate reductase (DHFR) led to a light-dependent dihydrofolate reductase activity (Lee et al 2008).…”
Section: Application Of Light-sensitive Modules In Synthetic Biology mentioning
confidence: 75%
“…The light-regulated affinity was even increased about 64-fold in subsequent rounds of rational mutagenesis (Strickland et al 2010). In a similar way, also a fusion of the LOV domain with the E. coli dihydrofolate reductase (DHFR) led to a light-dependent dihydrofolate reductase activity (Lee et al 2008).…”
Section: Application Of Light-sensitive Modules In Synthetic Biology mentioning
confidence: 75%
“…Recent studies have also shown that engineering can increase allosteric potential, enhancing inhibition of phosphofructokinase by phosphoenolpyruvate (34). An allosteric potential can even be engineered into enzymes where previously one did not exist (35). Nature has found mutations that constitutively activate allosterically regulated enzymes, as is well known in phosphorylation cascades contributing to tumorigenesis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Homologous protein sequence alignment (44 -46) or analysis of the covariance of the NMR chemical shifts (47) has predicted long range protein communication networks that agree with experimental observations. Some of these analyses have facilitated protein engineering (48). In the present study, we combined MD and mutagenesis to identify a long range communication network related to the activation of a key virulence factor derived from a bacterial pathogen.…”
Section: Discussionmentioning
confidence: 99%